Handbook of solvents - Ash, Michael; Ash, Irene (Synapse Information Resources, 2013)
This book provides comprehensive information on approximately 3000 trade name and generic solvent chemicals. Solvents are essential components in formulating a wide range of products because of their ability to clean, dissolve, suspend, and extract other chemicals or materials without changing their composition. This reference contains comprehensive coverage of the many solvents that are used in industry throughout the world and will serve as an invaluable ingredient selection tool for formulators, industrial and environmental chemists, manufacturers, product managers, safety regulators, purchasing agents, and chemical distributors as well as any professional associated with the processing and formulation industries. --